2014
DOI: 10.1093/hmg/ddu576
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dipeptide repeat protein in the molecular pathogenesis of c9FTD/ALS

Abstract: The expansion of the GGGGCC hexanucleotide repeat in the non-coding region of the chromosome 9 open-reading frame 72 (C9orf72) gene is the most common cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) (c9FTD/ALS). Recently, it was reported that an unconventional mechanism of repeat-associated non-ATG (RAN) translation arises from C9orf72 expansion. Sense and anti-sense transcripts of the expanded C9orf72 repeat, i.e. the dipeptide repeat protein (DRP) of glycine-alanine (poly-GA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
168
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(192 citation statements)
references
References 61 publications
24
168
0
Order By: Relevance
“…The construct containing 50 GP repeats was obtained through spontaneous contraction of a construct containing 100 GP repeats [kind gift from M. Yamakawa (Keio University School of Medicine, Tokyo, Japan)] [52]. Sequences from all constructs can be provided upon request.…”
Section: Plasmids and In Vitro Rna Transcriptionmentioning
confidence: 99%
“…The construct containing 50 GP repeats was obtained through spontaneous contraction of a construct containing 100 GP repeats [kind gift from M. Yamakawa (Keio University School of Medicine, Tokyo, Japan)] [52]. Sequences from all constructs can be provided upon request.…”
Section: Plasmids and In Vitro Rna Transcriptionmentioning
confidence: 99%
“…Of the distinct p62-positive, TDP43-negative histopathological inclusions in the cerebellum, the dipeptide protein, poly-GA, is the main prevalent constituent. [7][8][9] All slides were counterstained with hematoxylin to visualize neurons. Severity of pathological inclusions in Purkinje and granule cells in each section was semigraded quantitatively using an Olympus microscope at 2003 magnification and a 4-point severity scale (0 5 none; 1 5 mild; 2 5 moderate; 3 5 severe).…”
Section: Preparation Of the Cerebellum And Histopathological Assessmentsmentioning
confidence: 99%
“…5 These pathological inclusions were found to contain dipeptide repeat proteins, 6 the poly-GA protein in particular. [7][8][9] Another finding focusing attention on the cerebellum in ALS is the discovery that intermediate repeat expansions (27-33 repeats) in the ataxin-2 gene (ATXN2) is a major risk factor for ALS, with a prevalence of 2%. ; 10 Large expansions in the ATXN2 gene (>33 glutamine repeats) give rise to spinocerebellar ataxia type 2 (SCA2), 11 a cerebellar syndrome characterized by early and pronounced Purkinje cell degeneration in the lateral cerebellar hemispheres and vermis.…”
mentioning
confidence: 99%
“…Alongside holistic methylation studies, others have focused on the methylation status of the C9orf72 gene promoter, shown to be hypermethylated in expansion carrier ALS and FTD patients [19-22]. Such aberrant methylation has been suggested to be a disease modifier acting through a loss-of-function [23] rather than a toxic gain-of-function mechanism [12, 24]. …”
Section: Introductionmentioning
confidence: 99%